The Effect of Burnout Syndrome on Social Media Addiction: The Case of Healthcare Workers - Avşar Aslan; Nesrin Öğüt; Enderhan Karakoç (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
AbstractSocial media is one of the communication tools whose using and prevalence has increased rapidly in recent years. In particular, the rapid development of information technology and the proliferation of smartphones have created the perfect environment for social media addiction, which affects all members of society, including health professionals. Available evidence suggests that the direct and indirect effects of social media addiction on human health may include, among other things, burnout. This study was conducted to reveal the impact of burnout syndrome on social media addiction. The study utilized purposive sampling technique; face-to-face survey technique was applied for data collection. The findings of the study show that the healthcare workers participating in the study have a moderate level of burnout syndrome and social media addiction. Social media addiction differs according to the gender of the participants. Again, it was found that there was no significant difference in burnout level according to gender, but there was a significant difference according to marital status. A significant difference was also found between the level of social media addiction and educational status. Another important result of the study is that there is a positive relationship and effect between social media addiction and burnout level.